2021
DOI: 10.3390/v13071281
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Profiles, Glycosylation Site Distribution and Codon Usage Bias of Human Papillomavirus Type 16

Abstract: Human papillomavirus type 16 (HPV16) is the most prevalent HPV type causing cervical cancers. Herein, using 1597 full genomes, we systemically investigated the mutation profiles, surface protein glycosylation sites and the codon usage bias (CUB) of HPV16 from different lineages and sublineages. Multiple lineage- or sublineage-conserved mutation sites were identified. Glycosylation analysis showed that HPV16 lineage D contained the highest number of different glycosylation sites from lineage A in both L1 and L2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Conversely, yeast glycans tend to be larger high mannosylated structures 73,74 . However, while L1 is traditionally thought to be pauci-glycosylated 75 , emerging data suggest that alterations in n-linked glycosylation may represent a key HPV diversification 76 . Thus, the use of glycosylated HPV in this study may be important to capture antibody responses to this evasive biology.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, yeast glycans tend to be larger high mannosylated structures 73,74 . However, while L1 is traditionally thought to be pauci-glycosylated 75 , emerging data suggest that alterations in n-linked glycosylation may represent a key HPV diversification 76 . Thus, the use of glycosylated HPV in this study may be important to capture antibody responses to this evasive biology.…”
Section: Discussionmentioning
confidence: 99%
“…A study analyzing numerous HPV 16 L1 sequences indicated that the A1 sublineage had the largest number of potential glycosylation sites. Some glycosylation sites were lineage‐specific with 27 glycosylation sites observed only in lineage A 127 . However, the relationship between glycosylation and HPV vaccine escape is not definite yet.…”
Section: Hpvmentioning
confidence: 97%
“…Some glycosylation sites were lineage-specific with 27 glycosylation sites observed only in lineage A. 127 However, the relationship between glycosylation and HPV vaccine escape is not definite yet. In addition, a mutation in connected regions of two loops could also induce structural changes since these antigenic epitopes of HPV are discontinuous.…”
Section: Limited Evidence and Mechanism Research Of Hpv Vaccine Escapementioning
confidence: 99%
“…Within many developing nations, cervical cancer emerges as a prevalent malignancy in women, with around 99.7% of affected individuals concurrently harboring HPV [4]. The classification of HPV is determined by its level of pathogenicity, categorizing it into high-risk and low-risk types [5]. Continual infection by high-risk human papillomavirus (HR-HPV) is strongly linked to the initiation and advancement of cervical cancer [6].…”
Section: Introductionmentioning
confidence: 99%